The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1210/jcem-50-1-204
|View full text |Cite
|
Sign up to set email alerts
|

Pinealectomy Abolishes Plasma Melatonin in the Rat

Abstract: Using gas chromatography-negative ionization mass spectrometry, plasma melatonin levels in pinealectomized and sham-operated rats were assessed. The pinealectomized rats consistently demonstrated an absence of plasma melatonin while the intact animals showed detectable amounts. This suggests that although melatonin may be formed in tissues other than a pineal gland, the contribution to plasma is of pineal origin. Thus, plasma melatonin levels can be used as a marker of circadian melatonin secretion by the pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(59 citation statements)
references
References 19 publications
7
51
0
1
Order By: Relevance
“…In this simple preparation, responses to pharmacological agents applied directly to the SCN can be assessed unambiguously against the normally invariant basal rhythm. Application of 1 nM of melatonin, which is near physiological concentrations [19], directly to the SCN in this brain-slice preparation can reset the neuronal circadian rhythms [23]. When the medium in the brainslice chamber is replaced between CT 10 and CT i 1 by a warmed, oxygenated melatonin solution, the time-ofpeak, and thus the phase of the rhythm, on the next day in vitro is advanced by 4 h (Fig.…”
Section: Circadian Changes In the Sensitivity Of Scn Rhythms To Phasementioning
confidence: 89%
“…In this simple preparation, responses to pharmacological agents applied directly to the SCN can be assessed unambiguously against the normally invariant basal rhythm. Application of 1 nM of melatonin, which is near physiological concentrations [19], directly to the SCN in this brain-slice preparation can reset the neuronal circadian rhythms [23]. When the medium in the brainslice chamber is replaced between CT 10 and CT i 1 by a warmed, oxygenated melatonin solution, the time-ofpeak, and thus the phase of the rhythm, on the next day in vitro is advanced by 4 h (Fig.…”
Section: Circadian Changes In the Sensitivity Of Scn Rhythms To Phasementioning
confidence: 89%
“…Previous investigations of pinealectomized animals revealed substantial levels of an immunoreactive substance that was interpreted to be melatonin [reviewed by Lewy et al,13]. We further suggested that assay specificity in rats could be partially verified by demonstrating abolition of melatonin levels following pinealectomy and that circulating levels of melatonin could therefore be used to assess human pineal melatonin production, adrenergic tone in the pineal, light sensitivity and the phase of the endogenous circadian pacemaker (ECP) [15].…”
Section: Lewymentioning
confidence: 99%
“…Our assay was also instrumental in enabling us to demonstrate that virtually all measurable melatonin in the circulation of rats and humans is derived from the pineal gland [13,14]. Previous investigations of pinealectomized animals revealed substantial levels of an immunoreactive substance that was interpreted to be melatonin [reviewed by Lewy et al,13].…”
Section: Lewymentioning
confidence: 99%
“…Animals were housed in groups of three to five, in clear plastic cages with food and water ad libitum. Rats were always sacrificed during the light phase of the light/dark cycle, between ZT6 and ZT8) (ZT, Zeitgeber time; ZT0 lights on), when the blood melatonin levels are the lowest (Lewy et al, 1980). All studies were carried out in accordance with the Guide for the Care and Use of Laboratory Animals as adopted and promulgated by the National Institutes of Health.…”
Section: Animalsmentioning
confidence: 99%
“…The effect of these ligands cannot be attributed to the presence of melatonin on the receptor, as at the time the animals were sacrificed, serum melatonin is very low (Lewy et al, 1980) and the effect was observed only during proestrus. The presence of MT 1 constitutively active receptors was previously demonstrated in rat arteries .…”
Section: Downloaded Frommentioning
confidence: 99%